The gut microbiota heterogeneity and assembly changes associated with the IBD - Sun, Yang; Li, Lianwei; Xia, Yao; Li, Wendy; Wang, Kunhua; Wang, Lan; Miao, Yinglei; Ma, Sam (Scientific reports, 2019)
Inflammatory bowel disease (IBD) is an immunologically mediated disease and may be caused by abnormal immunological response to gut microbes. Although several studies on the ecological changes associated with IBD, such as community diversities, were reported, no previous studies have investigated the changes in the spatial heterogeneity and the mechanism of community assembly of the gut microbiota associated with IBD. In the present study, we first applied the Taylor’s power law extensions to compare the community spatial heterogeneity between the gut microbial communities of the IBD patients and those of the healthy individuals. We found that the community spatial heterogeneity of gut microbiota in IBD patients is slightly lower than in the healthy individuals. This finding suggests that IBD may lower the spatial heterogeneity of gut microbiota, possibly via lowering the abundance of dominant species. We further applied the neutral theory of biodiversity to comparatively investigate the community assembly and diversity maintenance of the gut microbiota with and without IBD, and our application suggested that deterministic factors such as host immunity should be dominant forces shaping gut microbiota assembly, and diseases such as IBD may not be strong enough to change the trend set by the deterministic host factors.